Labor flexes its muscle for tobacco industry (Tufts Archival Research Center, 2007)
Boston Globe article discussing organized labor's legislative support of the tobacco industry. Discusses reasons for the compatibility between the concerns of the two groups. Cites statistics showing blue collar workers are more likely to suffer from smoking-related health issues